Interactions between an extrafloral nectar-feeding predator and ants and their effects on pest control - Iasczczaki, Rafael Stempniak (2022)
The strategical adding of plants species that provide alternative foods (nectar, pollen, alternative prey) can positively affect the diversity and densities of natural enemies of crop pests and consequently improve the biological control they offer in agricultural fields. Extrafloral nectar-producing Inga trees are often consorted to coffee agroforestry systems and, due to this nectar, they can attract and arrest a diversity on natural enemies that contribute to the control of coffee pests. Mites from the Phytoseiidae family are key natural enemies of coffee pest mites, but no study has investigated whether Inga extrafloral nectar increases the performance of predatory mites from coffee ecosystems. During the chapter I of my dissertation, I assessed whether the extrafloral nectaries of Inga edulis Mart. (Fabaceae) can be considered a suitable nutritional resource for the predatory mite Amblyseius herbicolus (Chant) (Acari: Phytoseiidae), one of the most frequent phytoseiids on Brazilian coffee crops. We found that feeding on extrafloral nectar allows for development and survival of A. herbicolus, but not reproduction. Furthermore, we speculated that the various natural enemies attracted to and feeding on the nectar of Inga are likely to interact with each other and some interactions within this community, e.g., hyperpradation and intraguild predation, may be detrimental for some species. Ants, for example, are known to interact strongly with plants through extrafloral nectar and they are important natural enemies of crop pests. They can aggressively defend nectar-producing plants towards other arthropods, including natural enemies and pollinators. Because the predatory mite that I investigated here also feeds on the Inga nectar, during the chapter II I provide the first study on the interaction between the most common ant species that visit extrafloral nectaries from Inga trees, i.e., Camponotus rufipes (Fabricius, 1775), Camponotus crassus Mayr, 1862 and Wasmannia auropunctata (Roger, 1863) and the mite A. herbicolus. My results showed no evidence that ants attacked and killed eggs, juveniles or adults of the predatory mite, either with or without Inga nectar present. Therefore, I suggest that an extrafloral nectar-producing plant can simultaneously benefit ants and predatory mites, which control different coffee pest species. In conclusion, the presence of Inga and other plants producing extrafloral nectar may improve the performance and biological control by predatory mites and ants in coffee fields and perhaps in other agroecosystems. Keywords: Alternative food items; Ant-mite interactions; Arthropod-plant interactions; Natural pest control; Nectar producing plants.